The Hero and Villain Gender Stereotypes in Jumbo Animation Film - Necholas David (Kata Kita: Journal of Language, Literature, and Teaching, 2026)
This article examines gender stereotypes in the depiction of the hero and villain in the Indonesian animated film Jumbo (2025). Using qualitative textual analysis, the study evaluates the characters’ behavior through the theoretical lens of Stuart Hall’s concept of representation and Judith Butler’s gender performativity. The method involves deconstructing the speech acts and performative gestures of two main characters: Meri, the kind-hearted ghost, and Pak Rusli, the corrupt village chief. The findings indicate that the film constructs the characters’ identities through binary oppositions and repeated performative acts. Pak Rusli embodies masculinity defined by the abuse of institutional power, while Meri displays femininity limited to emotional acts and dependence on others. The study concludes that Jumbo ultimately reinforces normative gender ideology.